The Ethylene Signaling Pathway Negatively Impacts CBF/DREB-Regulated Cold Response in Soybean (Glycine max) - Robison, Jennifer D.; Yamasaki, Yuji; Randall, Stephen K. (Frontiers in Plant Science, 2019)
During cold stress, soybean CBF/DREB1 transcript levels increase rapidly; however, expected downstream targets appear unresponsive. Here we asked whether the ethylene signaling pathway, which is enhanced in the cold can negatively regulate the soybean CBF/DREB1 cold responsive pathway; thus contributing to the relatively poor cold tolerance of soybean. Inhibition of the ethylene signaling pathway resulted in a significant increase in GmDREB1A;1 and GmDREB1A;2 transcripts, while stimulation led to decreased GmDREB1A;1 and GmDREB1B;1 transcripts. A cold responsive reporter construct (AtRD29Aprom::GFP/GUS), as well as predicted downstream targets of soybean CBF/DREB1 [ Glyma.12g015100 (ADH), Glyma.14g212200 (ubiquitin ligase), Glyma.05g186700 (AP2), and Glyma.19g014600 (CYP)] were impacted by the modulation of the ethylene signaling pathway. Photosynthetic parameters were affected by ethylene pathway stimulation, but only at control temperatures. Freezing tolerance (as measured by electrolyte leakage), free proline, and MDA; in both acclimated and non-acclimated plants were increased by silver nitrate but not by other ethylene pathway inhibitors. This work provides evidence that the ethylene signaling pathway, possibly through the action of EIN3, transcriptionally inhibits the CBF/DREB1 pathway in soybean.